Peran Keluarga dan Lingkungan dalam Pendidikan Islam - Yohana, Anggi Atma; Shofiah, Vivik; Lestari, Yuliana Intan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Islamic education is an integral process that aims to form a perfect human being who is balanced in spiritual, intellectual, and social aspects. In this context, family and environment play a vital role as a foundation and reinforcement in the formation of children's character and morals. This paper examines in depth the synergistic role between the family as the first madrasah and the environment as the main supporter in Islamic education. Through a descriptive qualitative approach, this paper highlights how families provide education through role models, habits, and supervision, while environments such as schools, communities, and social media help strengthen Islamic values through social and cultural interactions. A case study of a student named Anita shows the success of Islamic education that is harmonious between the roles of parents and the surrounding community. The results of the discussion emphasize that the success of Islamic education cannot be separated from the collaboration between the micro (family) and macro (community and school) environments. Thus, the synergy of the two is the key to forming a generation of Muslims who have noble morals and are resilient in facing the challenges of the times.